History of sex trafficking, recent experiences of violence, and HIV vulnerability among female sex workers in coastal Andhra Pradesh, India. - Gupta, Jhumka; Reed, Elizabeth; Kershaw, Trace; Blankenship, Kim M (International journal of gynaecology and obstetrics: the official organ of the International Federation of Gynaecology and Obstetrics, 2011)
To estimate the prevalence of sex trafficking as a mode of entry into sex work, and to examine associations between sex trafficking and recent violence experiences and HIV vulnerability among female sex workers (FSWs).
Keywords: Adult; Condoms; Cross-Sectional Studies; Female; HIV Infections; Human Rights Abuses; Humans; India; Prevalence; Prostitution; Unsafe Sex; Violence; Young Adult